Evaluation and degrowth’s upgrades, of sharing economy's contribution to citizens’ well-being in Gothenburg - GKAGKALIDIS, GRIGORIOS (My University, 2022)
Based on the problematic nature of growth, alternative solutions have been purposed in the framework of either growth led economic systems that attempt to reduce growth’s drawbacks or promote post-growth concepts as a compass of human development. By acknowledging that sharing economy has been part of these alternative concepts and the number of multiple reasons that are pinpointing in researching the socio-economic and societal aspects of the each of those concepts as the precondition in order to reform the current values systems of growth is socioeconomic and not sociotechnical (Khmara & Kronenberg, 2020), sharing economy and its contribution to well-being has been chosen as a topic to be investigated. This thesis utilizes a web survey on 960 people that was taken place on April 2021 and conducts a quantitative analysis of the socioeconomic factors and reasoning on why somebody would use sharing economy. In parallel, a qualitative analysis of the answers of citizens were conducted, on what comes to their mind when they hear the term sharing economy. All this analysis comes together and acts as a map for degrowth practices to be promoted to either amplify sharing initiatives in areas of Gothenburg with certain characteristics that already perceive sharing economy as something good for their well-being or attempt to introduce degrowth practices in the form of sharing initiatives in areas that they do not think that sharing economy contributes to their well-being. To analyse the relationship between socio-economic factors, answers given and the codes that were created, the software MAXQDA was used alongside with Microsoft Excel. Two groups of three codes were created to investigate if respondents’ approach was (neutral/negative/positive) towards sharing economy and what element do they think that sharing economy consist of (social, utilitarian, both). The results created the following approaches to enhance sharing economy that contributes to people’s well-being. In the first case, introduced degrowth practices are based on specific factors that are associated with positive citizens’ attitude towards sharing economy and contribution to their well-being. In this case, Centre is chosen as the area due to its highest level of trust which relates to low preference in answer 12 (I do not want to use sharing economy), and level 3 of education (the highest) is observed. A second choice is to amplify sharing initiatives in Southwest area for its specific characteristics. As a third choice, it was attempted to alleviate areas that perceived sharing economy as a non-contributor in their well-being and this is the area of Hisingen. Specific initiative to be amplified, like Bike Kitchen is purposed in the first case, for the second case an initiative with specific characteristics according to the area was proposed and in the third case an initiative that promotes sustainable consumption based on relational goods. In the end, it can be said that sharing economy and degrowth follows some of the same principles and goals (Hobson & Lynch, 2016). It is believed that sharing initiatives will help communities to be resilient and more coherent and contribute to their citizens’ well-being because sharing is not sole phenomenon, it interacts with people and act as incubator of development and well-being.
Keywords: Sharing economy; Well- being; Degrowth